Analysis of Metabolic Indices in Regions of Abnormal Perfusion in Patients with High-Grade Glioma - Lupo, J.M.; Cha, S.; Chang, S.M.; Nelson, S.J. (American Journal of Neuroradiology, 2007)
BACKGROUND AND PURPOSE: MR spectroscopic imaging (MRSI) and dynamic susceptibility-contrast MR imaging (DSC-MR imaging) are functional in vivo techniques for assessing tumor metabolism and vasculature characteristics. Because tumor hypoxia is influenced by tortuous, degraded, swollen, and angiogenic tumor vasculature, regions of abnormal perfusion parameters should coexist with changes in lactate and creatine metabolite levels.MATERIALS AND METHODS: DSC-MR imaging and lactate-edited MRSI were performed on 38 treatment-naive patients with high-grade gliomas (17 grade III, 21 grade IV) before surgical diagnosis. Regions of abnormal perfusion were determined from peak height and percent recovery maps for each voxel within the spectroscopic imaging volume. Choline, creatine, and lactate levels within voxels experiencing only abnormal peak height (aPH), only abnormal recovery (aRec), and both abnormal peak height and recovery (aPH+aRec) were determined and compared to the surrounding T2 hyperintensity (T2h) and normal-appearing white matter.RESULTS: There were decreasing trends in volume from aPH to aRec to aPH+aRec regions for both grade III and grade IV gliomas. Grade IV gliomas exhibited significantly elevated choline in all abnormal perfusion regions, with reduced creatine and increased lactate in the aRec region relative to the surrounding T2h. Grade III gliomas showed trends toward increased creatine within the aPH region and reduced levels within the aRec region.CONCLUSION: Depressed creatine and elevated lactate levels confirmed the lack of oxygenation within regions of compromised vascular integrity. Identification of regions with leaky or dense vasculature and metabolic markers of hypoxia and cellular proliferation could be useful in determining the more aggressive part of the tumor for targeting, monitoring, and assessing effects of treatment.